Cytomegalovirus (CMV) infection and risk of mortality in allogeneic hematopoietic stem cell transplantation (Allo‐HSCT): A systematic review, meta‐analysis, and meta‐regression analysis. Issue 9 (24th July 2019) - Giménez, Estela; Torres, Ignacio; Albert, Eliseo; Piñana, José‐Luis; Hernández‐Boluda, Juan‐Carlos; Solano, Carlos; Navarro, David
Abstract : Controversy surrounds the potential association between cytomegalovirus (CMV) infection and increased risk of mortality after allogeneic hematopoietic stem cell transplantation (Allo‐HSCT). A systematic literature search was conducted using the PubMed, EMBASE, and Web of Science databases, assessing the association between CMV infection, as documented by the pp65 antigenemia assay or by polymerase chain reaction (PCR) using blood specimens, and overall mortality (OM) and nonrelapse mortality (NRM) in the allo‐HSCT setting. Pooled effects were estimated using the generic inverse variance random effects model. Heterogeneity was evaluated by Cochrane's Q test and I 2 statistics. The source of heterogeneity was investigated by meta‐regression and subgroup analyses. Twenty‐six of 1367 studies fulfilled eligibility criteria. CMV infection identified by PCR monitoring was significantly associated with an increased risk of OM and NRM (hazard ratio 1.47, 95% confidence interval [1.20‐1.81], P ≤ .001; hazard ratio 1.68, 95% confidence interval [1.14‐2.49], P = .05, respectively). In this setting, the use of preemptive antiviral therapy (PET) resulted in a twofold increased risk of OM and NRM. The estimated effect sizes were associated with allo‐HSCT modalities. Although our analyses point to an association between CMV infection and an increased risk of OM and NRM in allo‐HSCT recipients, the high heterogeneity across studies prevented drawing of robust conclusions on this matter. Abstract : The authors find a moderate association between CMV viremia and the risk of overall and nonrelapse mortality in allogeneic hematopoietic stem cell transplant recipients, which appears to be modulated by the transplant modality and the use of pre‐emptive antiviral therapy.